Behavioural investing : a practitioner's guide to applying behavioural finance - Montier, James (Chichester, England ; Hoboken, NJ : John Wiley and Sons, 2007)
"Behavioural Investing: A Practitioner's Guide to Applying Behavioural Finance explores the biases we face, the way in which they show up in the investment process, and urges readers to adopt an empirically based skeptical approach to investing. This book is unique in combining insights from the field of applied psychology with a thorough understanding of the investment problem. The content is practitioner focused throughout and will be essential reading for any investment professional looking to improve their investing behavior to maximize returns."--BOOK JACKET
SECTION I: COMMON MISTAKES AND BASIC BIASES -- Emotion, neuroscience and investing: investors as Dopamine addicts -- Part man, part monkey -- Take a walk on the wild side -- Brain damage, addicts and pigeons -- What do secretaries' dustbins and the Da Vinci Code have in common? -- The limits to learning -- SECTION II: THE PROFESSIONALS AND THE BIASES -- Behaving badly -- SECTION III: THE SEVEN SINS OF FUND MANAGEMENT -- A behavioural critique -- The folly of forecasting: ignore all economists, strategists, and analysts -- What value analysts? -- Why waste your time listening to company management? -- Who's a pretty boy then? Or beauty contests, rationality and greater fools -- ADHD, time horizons and underperformance -- The story is the thing (or the allure of growth) -- Scepticism is rare or (Descartes vs Spinoza) -- Are two heads better than one? SECTION IV: INVESTMENT PROCESS AS BEHAVIOURAL DEFENCE -- The Tao of investing -- PART A: THE BEHAVIORAL INVESTOR -- Come out of the closet (or, show me the alpha) -- Strange brew -- Contrarian or conformist? -- Painting by numbers: an ode to quant -- The perfect value investor -- A blast from the past -- Why not value? The behavioural stumbling blocks -- PART B: THE EMPIRICAL EVIDENCE: VALUE IN ALL ITS FORMS -- Bargain hunter (or it offers me protection) -- Better value (or the dean was right!) -- The little note that beats the market -- Improving returns using inside information -- Just a little patience: part I -- Just a little patience: part II -- Sectors, value and momentum -- Sector-relative factors works best -- Cheap countries outperform -- PART C: RISK, BUT NOT AS WE KNOW IT -- CAPM is crap (or, the dead parrot lives!) -- Risk managers or risk maniacs? -- Risk: finance's favourite four-letter word -- SECTION V: BUBBLES AND BEHAVIOUR -- The Anatomy of a bubble -- De-bubbling: alpha generation -- Running with the devil: a cynical bubble -- Bubble echoes: the empirical evidence SECTION VI: INVESTMENT MYTH BUSTERS -- Belief bias and the zen investing -- Belief bias and the x-system -- Confidence isn't a proxy for accuracy -- Belief bias and the zen of investing -- Dividends do matter -- Dividends, repurchases, earnings and the coming slowdown -- Return of the robber barons -- The purgatory of low returns -- How important is the cycle? -- Have we really learnt so little? -- Some random musings on alternative assets -- SECTION VII: CORPORATE GOVERNANCE AND ETHICS -- Abu Ghraib: lesson from behavioural finance and for corporate governance -- Doing the right thing or the psychology of ethics -- Unintended consequences and choking under pressure: the psychology of incentives -- SECTION VIII: HAPPINESS -- If it makes you happy -- Materialism and the pursuit of happiness
Includes bibliographical references (pages 667-676) and index
Keywords: Investments -- Psychological aspects; Finance -- Psychological aspects